2019
DOI: 10.1126/science.aau8722
|View full text |Cite
|
Sign up to set email alerts
|

Intense threat switches dorsal raphe serotonin neurons to a paradoxical operational mode

Abstract: Survival depends on the selection of behaviors adaptive for the current environment. For example, a mouse should run from a rapidly looming hawk but should freeze if the hawk is coasting across the sky. Although serotonin has been implicated in adaptive behavior, environmental regulation of its functional role remains poorly understood. We found that stimulation of dorsal raphe serotonin neurons suppressed movement in low- and moderate-threat environments but induced escape behavior in high-threat environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 31 publications
11
101
1
Order By: Relevance
“…54 In addition, serotonin stimulation enhanced behavior transiently within a few seconds during the high-threat condition. 54 Therefore, the transient activities of serotonin enhance or suppress movements in a contextdependent manner.…”
Section: Effects Of Transient Dopamine and Serotonin On Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…54 In addition, serotonin stimulation enhanced behavior transiently within a few seconds during the high-threat condition. 54 Therefore, the transient activities of serotonin enhance or suppress movements in a contextdependent manner.…”
Section: Effects Of Transient Dopamine and Serotonin On Behaviormentioning
confidence: 99%
“…Although the studies above reported transient effects of serotonin activation that apparently suppressed some aspects of behaviors, a separate study revealed that when PFC inputs onto the DR were stimulated with optogenetics, which are supposed to activate the DR, mice exhibited increases in effort‐related behavior during the forced‐swim test . A later study further investigated the potential of serotonin promoting vigorous behavior in some contexts . When mice were under high threat conditions, such as the tail‐suspension test, serotonin neurons exhibited rapid increases in activity, which were correlated with movement, but exhibited decreases in activity under low‐threat conditions .…”
Section: Effects Of Transient Dopamine and Serotonin On Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Brain development is a self-reinforcing process in which brain cells proliferate, differentiate, migrate, and connect functional neural circuit, especially primate-specific features of GABAergic interneuron development [210] on the basis of GABA content in diet. Survival depends on the selection of behaviors adaptive for environment; however, stimulation of dorsal raphe GABA neurons promoted movement in negative but not positive environments to promote environment-specific adaptive behaviors of serotonin [211]. Barley is a major crop in many developed countries [9]; GABA in barley grass suiting environmental extremes (cold, arid, and salt) can significantly increase, which can improve cognition and prevent 12 chronic diseases [6].…”
Section: Human Health Contribution Of Functional Ingredients In Barleymentioning
confidence: 99%
“…To this end, a recent study reported metabolic signatures consistent with compromised mitochondrial function in male combat veterans, even when controlling for common confounding variables (Mellon et al, 2019). In addition, repeated shock, proposed as a model of PTSD, has been reported to cause acute alterations in mitochondrial function of hippocampal tissue of adult male rats (Seo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%